The Entrepreneurial Firm as a Context for Employee Work: Novelty Creation in Small Organizations from a Multilevel Perspective - Fischer, Sebastian (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2012)
Entrepreneurs and entrepreneurial firms are a frequent research topic in psychological research. However, the focus of this research has largely been on the entrepreneur as a person and on the entrepreneurs’ strategy for the business. By contrast, the entrepreneur as a leader and the entrepreneurial firm as a work environment for employees have received little attention. Therefore, this dissertation aims to integrate theoretic thoughts from organizational behavior research into entrepreneurship research. Specifically, I will focus on novelty creation within entrepreneurial firms and organizational phenomena which provide a context for employees in novelty creating activities. This dissertation adds to the literature as it provides insight in the effects of work environment facets on employees’ engagement in novelty creating activities in entrepreneurial businesses. In three empirical chapters, I will focus first on the effects of entrepreneurial orientation on efficiency of employee work in innovation projects. Second, I will look at a facet of organizational culture, the error management culture, and its effects on individual learning of employees. Last, I will focus on occupational roles of employees within small businesses and effects of these roles on responses to a questionnaire and on work in innovation projects. In all three empirical chapters I test my hypotheses in a sample of N = 40 entrepreneurial businesses and employees within these businesses. For my chapter on occupational roles this sample is complemented by two additional samples of college students. In sum, results indicate that the entrepreneurial business in all three chapters exerts significant influences on employee work. Furthermore, I show that employee participation in novel activities is positive for entrepreneurial businesses (Chapter 2: Correlation between employees’ and entrepreneurs’ evaluation of innovation project effectiveness: r = .44; p < .01; Chapter 3: Correlation between organizational level leaning and organizational growth in sales: r = .35; p < .01). Therefore, I suggest that research on the entrepreneurial firm as a context for work may contribute to our knowledge on success factors in entrepreneurship, and may therefore be a relevant direction of future research. Especially, it may be fruitful to investigate aspects of work in which entrepreneurial firms may differ from other, less entrepreneurial organizations.

Unternehmer und deren Unternehmen sind ein häufiger Untersuchungsgegenstand psychologischer Forschung. Allerdings liegt hierbei der Fokus meist auf dem Unternehmer als Person oder auf der Strategie eines Unternehmens und deren Zusammenhang mit dem Erfolg des Unternehmens. Dagegen hat der Unternehmer als Führungsperson für Mitarbeiter bisher relative wenig Aufmerksamkeit auf sich gezogen. Daher versucht diese Dissertation, theoretische Gedanken aus der Forschung zu organisationalem Verhalten in die Forschung zu Unternehmertum zu integrieren. Insbesondere fokussiere ich dabei auf Prozesse der Erstellung neuer Produkte oder Dienstleistungen. Das Unternehmen stellt den Kontext für solche Prozesse dar. Damit trägt meine Dissertation zur Literatur im Bereich Unternehmertum bei indem sie einen Einblick in interne Prozesse von Unternehmen bietet. In drei empirischen Kapiteln analysiere ich zunächst den Effekt von unternehmerischer Orientierung auf die Effizienz der Arbeit von Mitarbeitern in Innovationsprojekten. Anschließend untersuche ich eine Facette der Unternehmenskultur, die Fehlermanagementkultur, und ihre Effekte auf das Lernen von Mitarbeitern. Zuletzt untersuche ich unterschiedliche Berufsrollenverständnisse von Mitarbeitern der Unternehmen, und deren Effekt auf die Selbstbewertung von Innovativität. In allen drei Kapiteln teste ich Hypothesen in einer Stichprobe bestehend aus 40 Unternehmen und Mitarbeitern dieser Unternehmen. Für das Kapitel zu Berufsrollenverständnissen wird diese Stichprobe um eine Studentische Stichprobe erweitert. Insgesamt zeigen die Ergebnisse der Dissertation, dass Unternehmen einen Einfluss auf das Verhalten und die Selbstbewertung eigener Fähigkeiten im Bereich Innovation ausüben. Ich zeige weiterhin dass diese Einflüsse wichtig sind für Unternehmen: In Kapitel 3 erweist sich, dass Mitarbeitereinschätzungen der Effektivität der eigenen Arbeit in Innovationsprojekten von Führungskräften geteilt werden, d.h. Hinweise zur Verbesserung der Effizienz in Innovationsprojekten können aus der Forschung abgeleitet werden. Diese Dissertation weist darauf hin, dass Forschung stärker auf Beziehungen innerhalb von Unternehmen blicken könnte, um langfristig besser zu verstehen warum einige Unternehmen weiterbestehen, während andere scheitern. Insbesondere im Innovationszusammenhang könnten interne Prozesse einen größeren Einfluss haben, als dies von bisheriger Forschung angenommen wurde.
Kleinunternehmen als Umfeld für angestellte Tätigkeiten: Die Entwicklung von Neuigkeiten in kleinen Organisationen aus seiner Mehrebenen-Perspektive
Keywords: 330 Wirtschaft